2000
DOI: 10.1055/s-2000-6298
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Stereoselective C-C, C-O, C-N and C-S Couplings via Microwave Accelerated Palladium-Catalyzed Allylic Substitutions

Abstract: Palladium-catalyzed substitution of cyclohex-2-en-1-yl ethyl carbonate with neutral C-, O-, and N-nucleophiles was achieved in 1-2 minutes using microwave flash heating. Enantioselectivities up to 96% were observed. Ionic nucleophiles tended to result in lower ee. With S-nucleophiles problems with the stability of the nucleophile were encountered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 9 publications
1
20
0
1
Order By: Relevance
“…11.38) [55]. These reactions, when irradiated for 1 min with temperatures up to 100 8C, delivered yields (91±96 %) and ee values (94±95 %) identical with those performed in closed vessels in an oil bath at 100 8C for 5 min.…”
Section: Asymmetric Catalysissupporting
confidence: 52%
See 1 more Smart Citation
“…11.38) [55]. These reactions, when irradiated for 1 min with temperatures up to 100 8C, delivered yields (91±96 %) and ee values (94±95 %) identical with those performed in closed vessels in an oil bath at 100 8C for 5 min.…”
Section: Asymmetric Catalysissupporting
confidence: 52%
“…(11.37), has recently been reported to yield high ee under single-mode microwave irradiation [54,55]. The use of this P,N-ligand catalytic system resulted in even higher ee than the P,P-ligand BINAP [56].…”
Section: Asymmetric Catalysismentioning
confidence: 98%
“…Despite these limitations, a number of very impressive enantioselective reactions involving chiral transition-metal complexes have been described. The research groups of Moberg, Hallberg, and Larhed reported on microwave-mediated palladium- [115,116] and molybdenum-catalyzed [117][118][119] asymmetric allylic alkylation reactions involving neutral carbon, nitrogen, and oxygen nucelophiles in 2000. Both processes were carried out under non-inert conditions and yielded the desired products in high chemical yield and with typical ee values of > 98 %.…”
Section: Asymmetric Allylic Alkylationsmentioning
confidence: 99%
“…Although providing a direct measurement of the temperature in the reactor it is not robust enough for daily use and handling, especially under reaction conditions that may be relevant in organic synthesis applications [2223]. …”
Section: Discussionmentioning
confidence: 99%